2021
DOI: 10.3390/en14113034
|View full text |Cite
|
Sign up to set email alerts
|

Digitalisation and Innovation in the Steel Industry in Poland—Selected Tools of ICT in an Analysis of Statistical Data and a Case Study

Abstract: Digital technologies enable companies to build cyber-physical systems (CPS) in Industry 4.0. In the increasingly popular concept of Industry 4.0, an important research topic is the application of digital technology in industry, and in particular in specific industry sectors. The aim of this paper is to present the tools used in the steel industry in Poland on its way to the full digitalisation that is needed for the development of Industry 4.0. The paper consists of two parts: a literature review and a practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 79 publications
(105 reference statements)
0
37
0
Order By: Relevance
“…In terms of digitalization, steel producers are linked with other industrial sectors. Currently, the process is not always easy because of problems with the usability of new technical solutions [99].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of digitalization, steel producers are linked with other industrial sectors. Currently, the process is not always easy because of problems with the usability of new technical solutions [99].…”
Section: Discussionmentioning
confidence: 99%
“…The issues of weights in the abovementioned Quality 4.0 were researched by the team led by A. Carvalho [65]. This research also pointed to the need to collect, process, and measure data in order to transform quality management towards Quality 4.0.…”
Section: Discussionmentioning
confidence: 99%
“…It is concluded that this method could be a contribution towards the transformation of the baking industry, towards Industry 4.0. In Industry 4.0, we digitalize all data, and analyze them using big data or artificial intelligence methods [65][66][67][68]. It is concluded that this method based on real data from bakeries will speed up the implementation of Industry 4.0 therein.…”
Section: Discussionmentioning
confidence: 99%
“…ICTs are in supply and storage processes, and in distribution and sales processes. Companies cooperating with steel mills create an integrated IT and computer environment with them (Gajdzik and Wolniak, 2021a;2012b). Integrated technologies (OT and IT) streamline the steel chain, from iron ore extraction, through steel production, to the distribution of steel products.…”
Section: The Theoretical Backgroundmentioning
confidence: 99%